Exploring Effects of the HEP (Homeostasis-Enrichment-Plasticity) Approach as a Comprehensive Therapy Intervention for an Infant with Cerebral Palsy: A Case Report - Balıkcı, Aymen (Journal of Child Science, 2022)
Cerebral palsy (CP) is a common non-progressive neurodevelopmental disorder which causes developmental disabilities in children. Varied interventions for CP exist to address medical and physical needs but with limited effectiveness evidence. Environmental enrichment (EE) is an animal model intervention for many neurodevelopmental disorders, including CP, with considerable positive effects. This case report defines the Homeostasis-Enrichment-Plasticity (HEP) approach, which is based upon principles of EE and ecological theories of development and describes its use to promote the developmental and functional skills of an infant with CP. Parent interviews and assessment data were completed before and after intervention. For the interested parameters data was gathered by developmental history, systematic observation of behaviors in the clinical setting and at home, Beck Anxiety Inventory (BAI), Infant-Toddler Symptom Checklist, the Sensory Proﬁle Infant/Toddler, Peabody Developmental Motor Scales-2, Gross Motor Function Measurement-88 (GMFM-88), the Gross Motor Function Classification System (GMFCS), and Pediatric Evaluation of Disability Inventory (PEDI). The HEP approach intervention was implemented one time per week for 12 months. Following the HEP approach intervention, self-regulation and sensory processing scores improved. GMFM-88 total score improved from 45/264 to 123/264. The Peabody found all gross motor (54–110), fine motor (65–117), and total motor quotient (119–227) scores improved after intervention. Post-intervention observations showed obvious gross motor progress with movement from GMFCS Level IV to Level I. Performance on the Functional Skills Scales and Caregiver Assistance Scales of PEDI also demonstrated notable improvements. BAI scores revealed low anxiety scores for both the mother (13/63 points) and father (14/63) before intervention. These scores did not change after intervention. A definition and detailed description of the HEP approach intervention is presented here for the first time. The case report demonstrated preliminary evidence for the effectiveness of the HEP approach on self-regulation, sensory processing, motor development, functional skills, and caregiver assistance with an infant with CP. Additional studies are needed to validate the findings.
Keywords: enriched environment; cerebral palsy; physical therapy; early intervention